Valuasi Potensi Wilayah Terhadap Minat Menjadi Migran Permanen di Yogakarta: Kasus mahasiswa asal NTT anggota KESA - Goma, Edwardus Iwantri (Pendidikan Geografi Fakultas Keguruan dan Ilmu Pendidikan Universitas Mulawarman, 2020)
Development disparity between two regions including development disparity of education is one of factors causing students migrate to Yogyakarta. This research was conducted in Yogyakarta with student respondents from NTT members of KESA. This study aims to identify the interests of students from NTT members of KESA becoming permanent migrants in Yogyakarta according to the regional potential valuation. The research method used was a mixed method using a survey method of 43 people and in-depth interviews with seven people. The data collected is presented in the form of: (1) descriptive using single frequency tables and cross tables, and (2) qualitative analysis to strengthen or support quantitative research. The results showed that the interest of students from NTT members of KESA based on the valuation of the potential Yogyakarta region and NTT region is known that most migrants who are interested becoming permanent migrants in Yogyakarta assess the potential of Yogyakarta region is better than potential of NTT region.